2014
DOI: 10.3133/ofr20141190
|View full text |Cite
|
Sign up to set email alerts
|

Downscaled climate projections for the Southeast United States: evaluation and use for ecological applications

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS. For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…This is consistent with other studies which found that guidance on selecting and using climate data is one of the most commonly cited needs from user groups (e.g., Maurer et al 2014). Although existing guidance documents compare different downscaled products (e.g., IPCC 2010; National Climate Assessment 2010; NOAA GFDL 2018; Trzaska and Schnarr 2014;Wilby et al 2004;Wootten et al 2014), these discussions are often not widely circulated among potential users of climate information and do not adequately interpret how non-climate experts could use this information. Interviewees expressed frustration at perceived hesitation from the climate science community to indicate which of the various scenarios, GCMs, or downscaled products might be the most appropriate for particular management questions.…”
Section: Guidancesupporting
confidence: 87%
“…This is consistent with other studies which found that guidance on selecting and using climate data is one of the most commonly cited needs from user groups (e.g., Maurer et al 2014). Although existing guidance documents compare different downscaled products (e.g., IPCC 2010; National Climate Assessment 2010; NOAA GFDL 2018; Trzaska and Schnarr 2014;Wilby et al 2004;Wootten et al 2014), these discussions are often not widely circulated among potential users of climate information and do not adequately interpret how non-climate experts could use this information. Interviewees expressed frustration at perceived hesitation from the climate science community to indicate which of the various scenarios, GCMs, or downscaled products might be the most appropriate for particular management questions.…”
Section: Guidancesupporting
confidence: 87%
“…The published datasets may exhibit differences arising from individual GCM bias, the characteristics of the training data, the specific implementation of downscaling algorithms, and data storage and representation issues. To our knowledge only one study, Wootten et al 24 , has compared an ensemble of downscaled datasets that are being distributed to the public. Wootten et al 24 focuses on data downscaled for the Southeastern USA, and is limited to data downscaled from only one GCM.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge only one study, Wootten et al 24 , has compared an ensemble of downscaled datasets that are being distributed to the public. Wootten et al 24 focuses on data downscaled for the Southeastern USA, and is limited to data downscaled from only one GCM. A similar study is needed for other regions, as well as for other GCMs and downscaling methods.…”
Section: Introductionmentioning
confidence: 99%
“…• Evaluating the fidelity of downscaled climate data on simulated wheat and maize production in the southeastern U.S. (Cammarano and others, 2013) • Final memorandum-Synthesis of climate model downscaling products for the Southeastern U.S. (Boyles, 2015) • Downscaled climate projections for the Southeast U.S.: Evaluation and use for ecological applications (Wootten and others, 2014) • Fact Sheet: Downscaled climate projections for the Southeast: Evaluation and use for ecological applications (Wootten and Furiness, 2015) Fiscal Year 2013…”
Section: Productsmentioning
confidence: 99%